Efficacy of omecamtiv mecarbil in heart failure with reduced ejection fraction according to N‐terminal pro‐B‐type natriuretic peptide level: insights from the GALACTIC‐HF trial. (16th January 2023) - Docherty, Kieran F.; McMurray, John J.V.; Claggett, Brian L.; Miao, Zi Michael; Adams, Kirkwood F.; Arias‐Mendoza, Alexandra; Cleland, John G.F.; Diaz, Rafael; Echeverria Correa, Luis E; Felker, G. Michael; Fonseca, Candida; Li, Jing; et al.
Abstract: Aim: N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) is predictive of both outcomes and response to treatment in patients with heart failure with reduced ejection fraction (HFrEF). The aim of this study was to examine the effect of the cardiac myosin activator omecamtiv mecarbil according to baseline NT‐proBNP level in the Global Approach to Lowering Adverse Cardiac outcomes Through Improving Contractility in Heart Failure trial (GALACTIC‐HF). Methods and results: The primary outcome was the composite of a worsening heart failure event (urgent clinic visit, emergency department visit, or hospitalization) or cardiovascular death. We prespecified analysis of the effect of treatment according to baseline NT‐proBNP (≤ median, > median), excluding individuals with atrial fibrillation/flutter (AF/AFL). Of the 8232 patients analysed, 8206 had an available baseline NT‐proBNP measurement. Among the 5971 patients not in AF/AFL, the median (Q1–Q3) NT‐proBNP level was 1675 (812–3579) pg/ml. Hazard ratios (HR) for the effect of omecamtiv mecarbil, compared with placebo, for the primary endpoint in patients without AF/AFL were: ≤ median 0.94 (95% confidence interval [CI] 0.80–1.09), > median 0.81 (0.73–0.90) ( p ‐interaction = 0.095); for the overall population (including patients with AF/AFL) the HRs were ≤ median 1.01 (0.90–1.15) and > median 0.88 (0.80–0.96) ( p ‐interaction = 0.035). There was an interaction between treatment and NT‐proBNP, examined as a continuous variable, with greater effect of omecamtiv mecarbil on the primary outcome in patients with a higher baseline NT‐proBNP ( p ‐interaction = 0.086). Conclusions: In GALACTIC‐HF, the benefit of omecamtiv mecarbil appeared to be larger in patients with higher baseline NT‐proBNP levels, especially in patients without AF/AFL. Clinical Trial Registration: ClinicalTrials.gov Identifier NCT02929329; EudraCT number, 2016‐002299‐28.